(untitled) (Sains Humanika, 2021)
Online Social Networking (OSN) is one of the internet online applications that have grown rapidly in popularity in the recent years. Online Social Networking sites (ONSs) such as Facebook, Twitter, You Tube, Instagram, Keek and others are member-based internet communities that allow users to connect and share their profile information, pictures and videos to communicate with their online members. At this present time, there are few different types of electronic devices such as personal computers, tablets as well as the mobile phones facilitate and make easy millions of these modern use of OSN and the implications of the use behavior of OSN towards the studentsâ€™ academic performance. This study aims to figure whether the OSN has an impact or influence toward academic performance by indicating the numbers of research being done in the past for the said scope. The analysis toward those literatures is done by using three steps which are; identify relevant literature, classify the literatures to the precise category, and synthesize and analyze to meet the study objective. The result shows that not many researches have been done on the said scope throughout the range of six years and this show the limitation of research that likely to be used as reference. It can be concluded that the mentioned scope needed more attention, especially Primary Level. The potential for research study on this matter is vast as the Facebook users growing rapidly.Â Â